Longitudinal MLT wind structure at higher mid-latitudes as seen by meteor radars at central and Eastern Europe (13°E/49°E). Issue 10 (15th May 2019) - Korotyshkin, Dmitriy; Merzlyakov, Eugeny; Jacobi, Christoph; Lilienthal, Friederike; Wu, Qian
Highlights: MLT winds measured by SKiYMET radars at Collm (51°N, 13°E) and Kazan (56°N, 49°E). Regular seasonal changes in the difference between the wind parameters are observed. SPWs make a significant contribution to mean winds mostly in winter. Non-migrating tides considerably contribute to the difference between SDT winds. Abstract: The mid-latitude mesosphere and lower thermosphere (MLT) wind speeds measured by two SKiYMET meteor radars (MRs) at Collm (51°N, 13°E) and Kazan (56°N, 49°E) during 2016–2017 were analyzed to study longitudinal wind structures. The differences between monthly mean prevailing wind speeds and tidal amplitudes were compared with the corresponding differences obtained from TIMED/TIDI satellite winds and gradient wind speeds from the AURA/MLS instrument. It is shown that the MR wind difference between the two sites is statistically significant. The difference of the horizontal prevailing winds can be explained by a superposition of the background zonal flow, which is different at the two latitudes, with stationary planetary waves of different origin. Non-migrating tides contribute significantly to the difference of the semidiurnal tidal winds between the two sites.